Domestic Investment Incentives in International Trade Law. Issue 1 (February 2023) - Gourgourinis, Anastasios
Abstract: Domestic Investment Laws (DILs), a prominent tool of contemporary unilateral International Economic Law (IEL) in the context of the Liberal International Order (LIO), consistently provide for investment incentives as a key aspect of domestic industrial policies geared to influence investment location decisions. The various types of investment incentives include fiscal measures to attract investment, direct subsidies, and other regulatory measures aimed at creating favorable administrative and regulatory conditions for investment. This article analyzes how the provisions of the World Trade Organization (WTO) Agreements contain basic disciplines and set limitations for the distortive effects of investment incentives. It is argued that the relevance of WTO law for domestic investment incentives should not be under-stated; rather, DILs providing investment incentives should be treated as a limited exception to the ongoing move from international to domestic in the era of the LIO.